Health and safety at work – part of corporate social responsibility - Kornfeldová, Martina; Myšková, Renáta (Univerzita Pardubice, 2012)
Corporate Social Responsibility (further in the text only „CSR“) is a concept which is very used in current time and it has become a tool which helps to differentiate from other companies. It shows that in something „we are better“. It can help to strengthen a company image, competitiveness but also it can lead to reduce costs and increase in competitiveness. The aim of this text is to describe problematic of health and safety which belong among principles of CSR. In general, this topic is so important that each company should pay a great attention to it. This article focuses on companies which are active in the sector of construction.
Keywords: corporate social responsibility; health and safety; construction; green paper; labor code